Impeding Quorum Sensing Among the Intestinal Microbiota Impacts the Metastatic Rate of Colorectal Cancer - Matthew Dietz; Travis J. Gates; Rakesh Sikdar; Subbaya Subramanian; Mikael H. Elias; Christopher Staley (Cancer Medicine)
ABSTRACT Background The gut microbiota is associated with colorectal cancer (CRC) risk and CRC metastatic potential. However, the role of bacteria in CRC progression and metastasis remains unclear. Aims Here, we hypothesized that microbial communication, mediated through quorum sensing (QS), was a critical component regulating microbial functions related to cancer progression and metastasis. Materials & Methods To test this, male and female C57BL/6 mice were injected with organoids modeling aggressive colon cancer (CRC), carrying mutations in Apc, Kras, p53, and Smad4. Two groups of mice were treated with two different quorum quenching (QQ) lactonases (GcL or SsoPox) for 8 weeks (n = 10/group/sex). Fecal samples were collected weekly and characterized by Illumina next‐generation sequencing, with tissues collected during necropsy. Results Male mice treated with SsoPox had fewer metastases than control mice (χ2 = 3.206, p = 0.073), with no SsoPox‐treated male developing a metastasis. In contrast, female mice treated with SsoPox had more metastases than control mice (χ2 = 2.554, p = 0.110), and every female, SsoPox‐treated mouse that developed a primary tumor also developed metastasis by the experimental endpoint. However, QQ treatment was shown to minimally affect the gut microbiome composition. Similarly, no significant differences were observed in inflammatory response as assessed by immunofluorescent staining or fecal concentrations of immunoglobulin A, calprotectin, or lipocalin‐2. Differences in fecal short‐chain fatty acid concentrations also did not differ significantly. Discussion These results suggest that QQ treatment has a sex‐based effect on CRC metastatic rate. Conclusion Targeting communication among the gut microbiome may be a promising avenue for the development of CRC therapies that minimally impact microbial community composition and host immune response.